Effect of Additive Addition on RAP (Reclaimed Asphalt Pavement) as an Aggregate Substitution Against the Upper Surface Layer of The Road - Erwanto, Heri; Choiri, Aulia (Jakarta Global University, 2023)
As development in the field of infrastructure increases, it will require more materials of natural origin. The availability of materials from nature will be reduced and more limited. Meanwhile, the construction of infrastructure continues to run every year for the improvement and comfort of the community. With this, the importation of goods will also increase, especially for bulk asphalt materials, and it is possible that later the stone that becomes one of the main materials for hot asphalt mixture will also bring in from abroad. If waste from peeled asphalt (RAP) can be reused, it will automatically reduce the use of materials from nature and reduce import activities of goods which results in reduced state expenditure. The thesis task will discuss the reuse of peeled asphalt (milling) on the highway, starting from the benefits of RAP, the advantages of RAP, testing RAP materials and new materials, and how to produce RAP asphalt at the Asphalt Mixing Plant. The composition of the RAP used is 60% with SW1 rejunevile material of 3.8%, the addition of new aggregates of 40%, and the addition of new asphalt of 3.3%. The results of the compaction experiment in the field (trial compaction) which will be used for work reference are initial compaction (tandem roller 2 passing), intermediate compaction (tire roller 16 passing), and final compaction (tandem roller 1 passing), and the resulting density of hot mix beds of 98.36%.